Problematika Syafak dan Fajar dalam Menentukan Waktu Salat Isyak dan Subuh - Marataon Ritonga (University of Muhammadiyah Sumatera Utara, 2021)
The issue of syafaq and fajr resurfaced when the ISRN UHAMKA institute presented the results of its research related to the position of syafaq and fajr using Sky Quality Meter (SQM) and All Sky Camera (ASC). The results showed that the time for the Isha prayer was too long and the Fajr too early. Meanwhile, in Indonesia, the sun's altitude that has been used so far through the Ministry of Religion of the Republic of Indonesia and Islamic organizations ranges from -18 degrees for Isha prayer time and -20 degrees for fajr prayer time. The results of several studies that have been carried out have obtained varying results ranging from -13 to -20 degrees. The purpose of this study is to find out the problems that exist in determining the sun's altitude for the Isha and Fajr prayers time. This study shows that there are differences in criteria in determining the sun's altitude for the Isha and Fajr prayer times.